Deformation imaging by strain in chronic heart failure over sacubitril/valsartan: a multicenter echocardiographic registry (DISCOVER) ARNI. (14th October 2021) - Mandoli, G.E; Pastore, M.C; Giannoni, A; Benfari, G; Dini, F.L; Correale, M; Carluccio, E; Guaricci, A.I; Citro, R; Novo, G; Pasquini, A; Degiovanni, A; et al.
Abstract: Background: Sacubitril/valsartan changed the treatment of heart failure with reduced ejection fraction (HFrEF), due to the positive effects morbidity and mortality partly mediated by left ventricular reverse remodeling (LVRR). The aim of this multicenter study was to identify echocardiographic predictors of LVRR after sacubitril/valsartan administration. Methods: Patients with HFrEF requiring therapy with sacubitril/valsartan from 13 Italian centers were included. Echocardiographic indexes including speckle tracking echocardiography (STE) were used to predict LVRR (defined as LV end-systolic volume reduction and ejection fraction [LVEF] improvement >10% at follow-up) at 6 months follow-up as the primary endpoint. Changes in symptoms (NYHA class) and neurohormonal activations (N-terminal-pro-brain natriuretic peptide [NTproBNP]) were also evaluated as secondary endpoints. Patients with poor acoustic windows and missing data were excluded. Results: The final population consisted of 341 patients (mean age: 65±10 years; 18% female, median LVEF 30% [interquartile range:25; 34]. At 6 months follow-up, cardiac dimensions and function, including left heart STE parameters, improved (Table 1). Moreover, 82 (24%) patients showed early complete response (LVRR and LVEF ≥35%), 55 (16%) early incomplete response (LVRR and LVEF <35%), 204 (60%) no response (no LVRR and LVEF <35%) after 6 months of sacubitril/valsartan. Among patients with ischemic etiology, 68% (108) did not develop LV RR. Age, sex, general characteristics, baseline NYHA class and NT-pro BNP did not significantly differ between the groups.Conversely, baseline LV dimensions and LVEF showed significant differences between the groups (p<0.0001). Also, STE parameters were considerably better in group 1 compared to group 2 and 3 both at baseline and follow-up. Non-ischemic etiology, a lower left atrial volume index and a higher global longitudinal strain were all independent predictors of LVRR at multivariable logistic analysis (all p<0.01). With ROC and spline curves, LV GLS >−9.3% showed a good accuracy in predicting LV RR (Figure 1). LA strain was the best predictor of positive changes in NYHA class and NT-proBNP (all p<0.05). Conclusions: STE parameters at baseline could be useful to predict LVRR and early clinical response to sacubitril-valsartan, and thus could be used as a guide for treatment in patients with HFrEF. Funding Acknowledgement: Type of funding sources: None.